Infertility Due To Unilateral Testicular Hypoplasia with Excessive Sperm Abnormalities in a Male Dog - A Case Report - KUMAR, AJEET; HONPARKHE, M; SINGH, JAGIR; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
The present case report depicts infertility in male dog due to unilateral testicular hypoplasia withexcessive sperm abnormalities.
Keywords: Male infertility; Testicular hypoplasia; Sperm abnonnality; Canines